The edge of Mosby's sword : the life of Confederate Colonel William Henry Chapman - Bonan, Gordon B. (Southern Illinois University, 2009)
The Edge of Mosby's Sword is the first scholarly volume to delve into the story of one of John Singleton Mosby's most trusted and respected officers, Colonel William Henry Chapman. Presenting both military and personal perspectives of Chapman's life, Gordon B. Bonan offers an in-depth understanding of a man transformed by the shattering of his nation. This painstakingly researched account exposes a soldier and patriot whose convictions compelled him to battle fiercely for Southern independence; whose quest for greatness soured when faced with the brutal realities of warfare; and.